Modelo de adaptação evolucionária da vantagem da complexidade: um estudo de caso em uma escola técnica de saúde - Land, Aline Grams (2011)
Faced with an increasingly complex reality, permeated by uncertainty, classical thought is challenged with frequent intensity, while a new paradigm is on the rise. In this study, from the complex thought, it is considered that organizations are complex adaptive systems (CASs) that have characteristics such as autonomy, cooperation, aggregation, co-evolution and evolution. From this perspective, the goal of management is no longer eliminate uncertainty, but take advantage of the complexity of the system. Organizations as CASs are at different levels of complex evolutionary adaptation. Knowing the levels of organizational evolution and realize the situation in which an organization finds itself may assist in their development towards achieving higher levels of evolution. The Complexity Advantage Evolutionary Fitness Model, proposed by Kelly and Allison (1998) deals with the evolution of organizations as CASs. In this model are determined and characterized five levels of organizational evolution (Unconscious Self-Organization, Conscious Self-Organization, Guided Self-Organization, Quantitatively Guided Self-Organization and Consciously Competent Autopoiesis) according to seven variables (Scale, Momentum, Becoming, Belonging, Being, Autopoietic Behavior and Emergent System). Thus, the purpose of this study is to identify the level of complex evolutionary adaptation of the Technical Health School of UFPB according to The Complexity Advantage Evolutionary Fitness Model, proposed by Kelly and Allison (1998). The case study was used as a research strategy and data collection was performed by four different techniques: script-based interview, self-administered questionnaire, participant observation and secondary data research. The research subjects selected were members of the leadership and the framework servers of the Technical Health School of UFPB (THS/UFPB). In order to identify the level of complex evolutionary adaptation of THS/UFPB the seven variables of the model were analyzed by the triangulation of data obtained through interviews, direct observations, questionnaires and documentary research. From the conjoint analysis of the variables it was concluded that the organization is on the second level of complex evolutionary adaptation: Conscious Self-Organization. Once identified the level of complex evolutionary adaptation of the organization, actions were proposed for the organization to achieve higher levels of adaptation. These actions aimed at overcoming the remaining characteristics of the first level, and make allowances for the organization to evolve into the third level of complex evolutionary adaptation. Using a model created for-profit organizations to evaluate a nonprofit organization (public) is a limitation of this study. Thus, the development of a complex evolutionary adaptation model to nonprofit organizations, or more specifically to public education organizations is suggested. This research is also limited to members of the organization, future research could also consider the perceptions of students and other external stakeholders that relate to the organization.